Internalisasi Nilai-Nilai Spiritual Islam di SMK Plus Multazam - Nurjamal, Nurjamal; Munandar, Didih Syakir (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2019)
This study aims to determine the concept of internalization, internalization strategies and factors supporting and inhibiting the internalization of Islamic spiritual values ​​in SMK Plus Multazam. This study uses a qualitative descriptive method. The object in this study is the SMK Plus Multazam. Data collection techniques use interview, observation, and study documentation. The results showed that the concept of internalizing Islamic spiritual values ​​in SMK Plus Multazam was through the stage of value transformation, transaction value and the stage of transinternalization. Then, the strategy of internalizing Islamic spiritual values ​​in SMK Plus Multazam was carried out through planning contained in the school curriculum, local content subjects, extra-curricular, school education calendars and school rules. The implementation is through the strategy of habituation, punishment, exemplary, advice, and student awareness. Supporting factors in forming students' Islamic spiritual values ​​include daily worship, monthly worship and insidental worship as well as direct monitoring from the school and inhibiting factors including wrong association, families who are less supportive, lack of student awareness and the student's living environment.